Pengaruh Promotion Mix terhadap Minat Beli Konsumen D’bakule Di Pringsewu - Charina Azzahra Hasan; Aida Sari; Dwi Asri Siti Ambarwati (Goodwood Publishing, 2022)
Economic growth in Pringsewu Regency from 2016 to 2021 has increased, except for in 2020, it has decreased slightly due to the Covid-19 pandemic and even caused a decline in economic growth, but in 2021, it has increased again. Seeing the great opportunity in the restaurant business, many people are interested in starting this business, causing competition in the restaurant business to become increasingly stringent. Lesehan D'Bakule has challenges in this business competition in order to get the consumers interested in buying at Lesehan D'Bakule. Lesehan D'Bakule carried out a promotion strategy, namely the promotion mix. This research was conducted to determine the influence of the promotion mix's dimensions on the buying interest of Lesehan D'Bakule consumers in Pringsewu. This research has 5 variables, namely advertising variables, sales promotion variables, public relations variables, personal selling variables, and direct marketing variables. This research uses the non-probably sampling methode, with a sample of 100 respondents who know Lesehan D'Bakule in Pringsewu and are interested in visiting Lesehan D'Bakule in Pringsewu. The results of this study indicate that the variables of advertising, sales promotion, public relations, personal selling, and direct marketing have a significant positive effect on consumer buying interest.